2017
DOI: 10.3390/ijms18112429
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Non-Coding RNAs in Cytoplasmic Male Sterility in Flowering Plants

Abstract: The interactions between mitochondria and nucleus substantially influence plant development, stress response and morphological features. The prominent example of a mitochondrial-nuclear interaction is cytoplasmic male sterility (CMS), when plants produce aborted anthers or inviable pollen. The genes responsible for CMS are located in mitochondrial genome, but their expression is controlled by nuclear genes, called fertility restorers. Recent explosion of high-throughput sequencing methods enabled to study tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…We raise the question as to whether each of these Rf s is an idiosyncratic example that episodically emerged during plant-species diversification or is there a tendency or trend underlying Rf evolution. To approach this question, we will briefly review plant Rf s. Recent reviews on CMS, Rf and other types of male sterility will help to understand the progress of this research area [19][20][21][22][23][24][25][26][27][28][29][30][31][32]. This question has also been addressed from the viewpoint of evolutionary genetics (reviewed ib [33]).…”
Section: Introductionmentioning
confidence: 99%
“…We raise the question as to whether each of these Rf s is an idiosyncratic example that episodically emerged during plant-species diversification or is there a tendency or trend underlying Rf evolution. To approach this question, we will briefly review plant Rf s. Recent reviews on CMS, Rf and other types of male sterility will help to understand the progress of this research area [19][20][21][22][23][24][25][26][27][28][29][30][31][32]. This question has also been addressed from the viewpoint of evolutionary genetics (reviewed ib [33]).…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact nature of miRNAs with respect to CMS in plants remains elusive, discovery of miRNAs with possible implications for CMS induction is intriguing in this respect. The recent explosion of high-throughput sequencing has enabled genome-wide discovery of these regulatory molecules and their targets, implying their potential involvement in CMS [67]. Using this method combined with bioinformatic analysis, researchers have successively identified differentially expressed miRNAs and their targets between CMS lines and fertile lines of rice, B. juncea, cybrid pummelo (Citrus grandis) and many other species [45][46][47][48][49][50][51].…”
Section: Plos Onementioning
confidence: 99%
“…In this Special Issue, “Plant Mitochondria”, a total of 19 articles were accepted with 15 original research articles and 4 review articles broadly covering the field of plant mitochondrial research (Table 1). Manuscripts focused on protein synthesis and degradation [3,4,5,6], abiotic stress [7,8,9,10], OxPhos [11,12,13,14], protein import [15,16,17], ROS and antioxidants [18], and CMS [19,20].…”
mentioning
confidence: 99%
“…Both GMS and CMS are widely used in agricultural production for the production of hybrid crops that benefit from heterosis. In this Special Issue Štorchová [20] presents a comprehensive review of the role of non-coding RNA in the CMS of flowering plants, while Reddemann and Horn [19] presented research examining the role of atp9 in the male sterility of CMS PET2 in sunflower. Here they showed that CMS PET2, which has the potential to become an alternative CMS source for commercial breeding, has a duplicated atp9 with a 271-bp-insertion in the 5’ region of one of the atp9 genes which results in two unique open reading frames ( orf288 and orf231 ).…”
mentioning
confidence: 99%